Analisis Angkutan Umum Bus Pemadu Moda Di Kota Jayapura (Studi Kasus : Trayek Jayapura – Bandara Sentani) - Semuel Rorrong D. (Fakultas Teknik Universitas Cenderawasih, 2023)
The increase in Sentani Airport passengers is currently getting higher, in March 2022 Sentani Airport passengers increased by 25% compared to the same period in 2021. This increase in passengers has resulted in increased vehicle movement, especially four-wheeled vehicles. Currently, passengers at Sentani Airport tend to use private vehicles to go to the airport, thereby placing a burden on traffic. Therefore, public bus transportation is needed to support passenger travel to the airport. This study aims to determine the characteristics of passengers at Sentani Airport and the percentage of passengers who are willing to switch to using public bus transportation to support travel to/from the airport, and also to calculate the number of buses needed to serve the Jayapura route at Sentani Airport. The research location is located at Sentani Airport, Sentani District, Jayapura. The method used in this research is to conduct field surveys, namely distributing questionnaires to respondents and direct interviews with related parties. From the results of this study, the characteristics of Sentani airport passengers are dominantly traveling with tourism purposes. Passengers come from the upper middle class and are very concerned about the ease of use of the mode. The percentage of passengers who are willing to switch to using public bus transportation based on the criteria offered is 65%. The number of buses needed to serve the Jayapura route at Senatani Airport is 9 vehicles.